2012
DOI: 10.1097/prs.0b013e3182589df2
|View full text |Cite
|
Sign up to set email alerts
|

Giant Nevus Sebaceus

Abstract: Therapeutic, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several previous studies have demonstrated good outcomes following surgical treatment of nevus sebaceous [5,6]. Kyle J et al suggested that when planning surgical interventions for nevus sebaceous, it's crucial to consider facial aesthetics, aiming to maintain natural features like brow and hairline position while minimizing tension in key areas like the mouth, eyes, and ears [7]. In this case, due to her limited time and refusal for tissue expansion, we proceeded with excision of the lesion followed by full-thickness skin grafting for wound repair, resulting in excellent aesthetic outcomes and high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated good outcomes following surgical treatment of nevus sebaceous [5,6]. Kyle J et al suggested that when planning surgical interventions for nevus sebaceous, it's crucial to consider facial aesthetics, aiming to maintain natural features like brow and hairline position while minimizing tension in key areas like the mouth, eyes, and ears [7]. In this case, due to her limited time and refusal for tissue expansion, we proceeded with excision of the lesion followed by full-thickness skin grafting for wound repair, resulting in excellent aesthetic outcomes and high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%